2008
DOI: 10.1364/oe.16.009554
|View full text |Cite
|
Sign up to set email alerts
|

Near-field focusing properties of zone plates in visible regime - New insights

Abstract: Near-field focusing properties of zone plates are investigated in the visible regime by a 3-dimensional finite-difference time-domain method. It is shown that Frensel zone plates (FZPs) with metallic coatings can achieve subwavelength focusing in the visible wavelength. The characteristics of subwavelength focusing are found to be independent of the type of metal coatings used. All the FZPs exhibit similar shift in focal length and depth of focus when compared with classical calculations. These results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 14 publications
3
51
1
Order By: Relevance
“…FWHMx, is sensitive to the number of zones. Other authors also found the dependence of the focal lengths of a FZP on the zone numbers [34]. A straightforward understanding is that more zones integrated in the PL aperture, i.e.…”
Section: The Effect Of the Number Of Zones On The Pl Performancementioning
confidence: 84%
See 1 more Smart Citation
“…FWHMx, is sensitive to the number of zones. Other authors also found the dependence of the focal lengths of a FZP on the zone numbers [34]. A straightforward understanding is that more zones integrated in the PL aperture, i.e.…”
Section: The Effect Of the Number Of Zones On The Pl Performancementioning
confidence: 84%
“…However, diffraction may put the usefulness of the microlens in question in sub-2 m pixels [28]. Recent progress in nanotechnology and the theory of plasmonics has led to rapidly growing interest in the implementation of metallic optical elements on a nano-scale for light beam manipulation [29][30][31][32][33][34][35][36][37][38][39]. Especially, lots of theoretical predictions [30][31][32][33][34][35] and experimental demonstration [28,[36][37][38][39] have been reported on both one-dimensional (1D) and 2D PLs.…”
Section: Introductionmentioning
confidence: 99%
“…Through the last decade a lot of work was devoted to plasmonic focusing devices [2] which are in the form of planar metallic layers with holes, slits or surface corrugations either linear or circular [3][4][5][6][7][8][9][10][11]. Such structures, unlike classical, refractive lenses, concentrate light in a two-step process of photon-plasmon and plasmon-photon couplings.…”
Section: Introductionmentioning
confidence: 99%
“…Such structures, unlike classical, refractive lenses, concentrate light in a two-step process of photon-plasmon and plasmon-photon couplings. Such lenses can be classified as near-field devices concentrating evanescent field in the vicinity of the metal plate due to constructive interference of plasmons efficiently generated on circular grating [4][5], or far-field ones focusing light in the region distant a few wavelength from the lens due to phase matching of propagating beams scattered on the edges of slits or grooves at the back surface [6][7][8][9][10][11][12]. Generation an electromagnetic surface waves is strongly polarization dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Even though sub-wavelength focusing at optical frequencies has already been demonstrated through the use of Fresnel Zone plates with metallic coatings [5], what we propose here is a different design, based on the patterning of an opaque surface with a discrete set of dielectric cells, to create an inhomogeneous spatial distribution of the electric permittivity of the screen. In addition, the proposed approach suggests the possibility to achieve a subwavelength desired pattern at arbitrary distances.…”
Section: Introductionmentioning
confidence: 99%